Structure of clusters and building blocks in amylopectin from African rice accessions. (5th September 2016) - Gayin, Joseph; Abdel-Aal, El-Sayed M.; Marcone, Massimo; Manful, John; Bertoft, Eric
Highlights: Cluster and building block composition of African rice amylopectin was probed. African rice amylopectin has slightly larger clusters than Asian rice. A typical cluster in African rice amylopectin contains about five building blocks. The mean size of building blocks in African rice was larger than in Asian rice. The major type of building blocks in both types of rice is single branched. Abstract: Enzymatic hydrolysis in combination with gel-permeation and anion-exchange chromatography techniques were employed to characterise the composition of clusters and building blocks of amylopectin from two African rice ( Oryza glaberrima ) accessions—IRGC 103759 and TOG 12440. The samples were compared with one Asian rice ( Oryza sativa ) sample (cv WITA 4) and one O. sativa  ×  O. glaberrima cross (NERICA 4). The average DP of clusters from the African rice accessions (ARAs) was marginally larger (DP = 83) than in WITA 4 (DP = 81). However, regarding average number of chains, clusters from the ARAs represented both the smallest and largest clusters. Overall, the result suggested that the structure of clusters in TOG 12440 was dense with short chains and high degree of branching, whereas the situation was the opposite in NERICA 4. IRGC 103759 and WITA 4 possessed clusters with intermediate characteristics. The commonest type of building blocks in all samples was group 2 (single branched dextrins) representing 40.3–49.4% of the blocks, while groups 3–6 were found in successively lower numbers. The average number of building blocks in the clusters was significantly larger in NERICA 4 (5.8) and WITA 4 (5.7) than in IRGC 103759 and TOG 12440 (5.1 and 5.3, respectively).